Assessment of a Centerline Enthalpy Determination Method of Arcjet Wind Tunnel Flow - SUZUKI, Toshiyuki; SAKAMOTO, Kenichi; KATSURAYAMA, Hiroshi; SAKAI, Takeharu; TAKAGI, Yoichi (TRANSACTIONS OF THE JAPAN SOCIETY FOR AERONAUTICAL AND SPACE SCIENCES AEROSPACE TECHNOLOGY JAPAN, 2024)
The authors propose an enthalpy determination method for arcjet flows. The present method assumes the application combined with the spectroscopic emission measurement in a blunt probe shock-layer. The theoretical aspect of the proposed method is given in detail, emphasizing that thermal equilibrium is a necessary condition for the present method. Two types of arcjet wind tunnel experiments are performed to evaluate the accuracy and feasibility of the proposed method. Note that the spectroscopic emission from the arcjet flow fields is measured, which nearly satisfies the conditions necessary for the present method, and not from the shock-layer over the blunt body. For comparison, a computational fluid dynamics method is used to simulate the arcjet flows of interest. A comparison of the results indicates that the proposed method successfully predicts the centerline enthalpy.